STUDI NASKAH PEMIKIRAN DAKWAH (Muhammad Ahmad Al-Adawy) - IRHAMDI, MUHAMAD; NADI, KUS; ADI, ASRI (TASAMUH, 2020)
This article is focused on the concept of preaching Muhammad Ahmad Al-adawy in the book Da'watur rusul ila Allahi Ta'ala. This article is in the form of a literature review whose data is obtained from a literature study. Then the data obtained is then processed and analyzed using a socio-historical approach with a historical-elective-elimative method using a descriptive analytic model. The results of this study indicate that the concept of preaching al-Adawy does not see things about; First, be consistent to reveal the Purpose of the Stories of the Qur'an. Second, consistency in colonial thinking, this is due to the times passed by when Egypt was under the influence of British colonialism. Third, be consistent in revealing the historical roots of the stories of the Qur'an by consolidating verses with verses that talk about the history. Fifth, consistently pay attention to issues that are close to his time, such as problems with temples and graves.